Penerapan Ant Colony System untuk Penyelesaian Vehicle Routing Problem - Samuel Lukas; Arnold Aribowo; Hadinata Hadinata (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2007)
Many researchs have been conducted relating to optimization problems. This reseach proposes anotheralgorithm to solve optimation problem by implementing ant algorithm to Vehicle Routing Problem (VRP). TheVRP is an algorithm that works for multiple Traveling Salesmen Problems (TSP). The ant algorithm is analgorithm that simulating on how the behaviour of ant colony can find the shorthest path from one place toanother.There are some parameters to deal with this ant algorithm. To know the behaviour of these parameters,some experiments were conducted to know how good the parameters should be set to solve the given problem.Finally, the results of all experiments are also be reported.Keywords: Vehicle Routing Problem, ant Algorithm, Traveling salesmen Problem.